Lexical bundles in master's-level finance research articles - Ali Drouhamane, Alhassane, author; Nekrasova-Beker, Tatiana, advisor; Becker, Anthony, committee member; Bajtelsmit, Vickie, committee member (Colorado State University. Libraries, 2016)
Lexical bundles are a type of formulaic sequences mainly identified on the basis of their frequencies and ranges. They have been found to consistently serve important discourse functions in academic prose, where, for example, they are used to evaluate or to refer to the size of something (Hyland, 2008a). Their forms, functions and uses were also found to be different in different academic disciplines. The present study extends this line of investigation by directly investigating the extent to which the four-word lexical bundles relied upon in master’s-level finance research articles differ from or are similar to those used in other academic disciplines, including business texts. Analyzing a corpus of 1,034, 587 words, the researcher found that more than 60% of lexical bundles in master’s-level finance research articles were identified in earlier studies on lexical bundles used in academic prose. However, 33 lexical bundles identified in the current study were not identified in previous literature. Structurally, like in previous literature, most bundles were found to be noun phrase and prepositional phrase fragments. Functionally, most bundles analyzed in the present study include research-oriented and text-oriented bundles, like in previous literature. They, however, differ from the bundles identified in the business studies sub-corpus of Hyland (2008a) by including more research-oriented bundles.